Concept Analysis of The Development Gunung Api Merapi Museum Sleman Yogyakarta Based on Edu-Nature Historical Museum - Ni Made Sri Puspa Dewi Roels (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Mount Merapi Museum is one of the geological museums in Sleman Regency, Yogyakarta. Although as the only geological museum, the development of the museum is still not optimal as an educational tourism museum. This study aims to identify the tourist attraction of the Mount Merapi Museum and develop a conceptual model of development that is in accordance with the characteristics of the museum and the needs of tourists. This study uses a survey research approach. Data were collected by observation, interviews, and documentation. Informants were determined by purposive sampling. The data analysis method used interactive model analysis assisted by SWOT analysis. The results of this study are the identification of the strength of Mount Merapi Museum in the form of content attractiveness, architectural attractiveness, and attractiveness in the form of landscape and market analysis. This research also produces the concept of developing the Mount Merapi Museum based on the Edu-Nature Historical Museum, namely through the application of the interactive product concept. The interactive product development strategies are: dividing content into two thematic spaces, redesigning the plaza of the Mount Merapi simulation space, creating the best spots to enjoy the scenery, and involving the public in staging the story of Mount Merapi which is packaged in a show.